The Principality of Serbia’s Policy Towards the Albanians in the 1860s: An Analysis of Political Dynamics During a Decade of Change - Leovac , Danko Lj.; Ilić, Žarko D. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The paper discusses the evolving role of the Albanian population in the national strategies of the Principality of Serbia during the mid-19th century, particularly in relation to Ilija Garašanin’s influential policy document Načertanije. Garašanin’s vision emphasized cooperation with neighboring Balkan nations, recognizing that Serbia could not achieve its goals against Ottoman rule on its own. Although initially sidelined in Serbian plans, the Albanians were identified as potential worthy allies for establishing alternative trade routes and fostering loyalty to Serbia. The Serbian government attempted to gather intelligence on Albanian sentiments and establish connections with local leaders through a network of agents. Despite sporadic efforts and some initial successes, significant progress was limited until Russian influence began to shape Serbian policy more decisively. Ignatyev’s correspondence further underscored the importance of engaging with the Albanians, leading to renewed attempts to forge negotiations. The situation on the ground was markedly different: no substantial military organization had been established in Albania, and any potential action depended on unreliable agents who struggled to unite the Albanian chiefs.